Twittering Pupae of Papilionid and Nymphalid Butterflies (Lepidoptera): Novel Structures and Sounds. (23rd August 2018) - Dolle, Patrick; Klein, Philipp; Fischer, Ottmar W; Schnitzler, Hans-Ulrich; Gilbert, Lawrence E; Boppré, Michael
Abstract: Pupae of numerous Papilionidae and Nymphalidae produce twitter sounds when wriggling in response to mechanical stimulation. The structural basis comprises distinct pairs of sound-producing organs (SPOs) located at intersegmental membranes of the abdomen. They differ—as the twitters do—in sampled taxa of Papilioninae, Epicaliini, and Heliconiini. The opposing sculptured cuticular sound plates (SPs) of each SPO appear structurally the same but are actually mirror-images of each other. Results suggest that sounds are not generated by stridulation (friction of a file and a scraper) but when these inversely sculptured and interlocking surfaces separate during pupal wriggling, representing a stick-slip mechanism. Twitter sounds comprise series of short broadband pulses with the main energy in the frequency range 3–13 kHz; they can be heard by humans but extend into ultrasonic frequencies up to 100 kHz.